Characterization of the transcriptional regulatory region of the human dihydrolipoamide dehydrogenase gene. - Johanning, G L (1992)
Dihydrolipoamide dehydrogenase (E3; EC 1.8.1.4) is the common component of the three mammalian alpha-ketoacid dehydrogenase complexes and the glycine cleavage system. To study regulation of E3 gene expression, a 12-kilobase clone from a human leukocyte genomic library was isolated, and a 1.8-kilobase fragment containing part of the first intron, the first exon, and 1.5 kilobases of the 5' flanking region of the E3 gene was sequenced. The nucleotide sequence of the E3 promoter region revealed consensus sequences for several DNA binding proteins but no apparent TATA box or Sp1 sites. Although the 1.6-kilobase 5' flanking region has a low percentage of G+C (44%), the nucleotide sequence between +1 and -150 base pairs has a G+C content of 67%. Primer extension analysis showed a major transcriptional start site located 95 nucleotides upstream from the translation initiation codon. A series of 5' deletions from the E3 promoter-regulatory region were ligated to the bacterial chloramphenicol acetyltransferase (CAT) gene, and the resulting constructs were transfected into HepG2 cells. The longest E3 promoter-CAT construct had a relatively high level of CAT enzyme activity, and deletion of a promoter element between -769 and -1223 base pairs resulted in a 3-fold increase in reporter gene expression. These results suggest that the human E3 promoter has characteristics of housekeeping and facultative promoters and that a negative regulatory element is present between 769 and 1223 base pairs upstream from the transcription start site.